Can 8-weeks of Training Affect Active Drag in Young Swimmers? - Marinho, Daniel (2020)
Submitted by Daniel Marinho (dmarinho@ubi.pt) on 2020-02-12T22:35:30Z No. of bitstreams: 1 103 - jssm-09-71.pdf: 275083 bytes, checksum: 95aad40b126b265d2d98b23db402b659 (MD5)